The effect of social media usage on sustainable purchasing attitude with drive for environmental responsibility as a mediation variable - Lidya Hamdani Putri; Perengki Susanto (Universitas Negeri Padang, 2022)
The purpose of this study was to test the effect of Social Media Usage on SustainabIe Purchasing Attitude with Drive for EnvironmentaI ResponsibiIity as a mediating variable on consumers of The Body Shop in Padang City. In this study, the data used are primary data obtained from questionnaires and disseminated online with the help of Google Forms. The criteria for filling out the questionnaire are people who have bought and used The Body Shop products. A total of 200 respondents. The analysis tool uses the PLS (Partial Least Square) approach which is a Structural Equation Modeling (SEM) approach using SmartPLS 3.3.9 software. The results of the SmartPLS 3.3.9 analysis show that Social media usage has a positive and significant effect on Suistanable Purchasing Attitude as evidenced by the P-Value value of 0.001 < 0.005. SociaI media usage has a positive and significant effect on Drive for environmental responsibility as evidenced by the P-Value value of 0.000 < 0.005, then Drive for EnvironmentaI ResponsibiIity has a positive and significant effect on SustainabIe Purchasing Attitude with a P-Value of 0.000 <0.005, then the variable SociaI Media Usage on the Sustainable Purchasing Attitude variable in mediation by the Drive for EnvironmentaI ResponsibiIity variable has a positive and significant effect with a P-Value value of 0.000 < 0.005.